2017
DOI: 10.1017/s1366728917000219
|View full text |Cite
|
Sign up to set email alerts
|

Incidental vocabulary learning in a natural reading context: an eye-tracking study

Abstract: This study responds to the call for more ecologically valid psycholinguistic research (Spivey & Cardon, 2015) by examining how readers incidentally acquire multifaceted vocabulary knowledge while reading a long, authentic text. Using eye tracking, we explore how the processing of unfamiliar words changes with repeated exposure and how the repeated exposure and processing affect word learning. In two sessions, native and non-native English speakers read five chapters of an authentic English novel containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
146
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(183 citation statements)
references
References 62 publications
28
146
3
Order By: Relevance
“…The pattern of correlations between the learning gains and the TFD and ΔTFD values (see Table ) as well as the fact that there were significant learning effects in both tasks—grammaticality judgment task, t (19) = 4.34, p < .001, and sentence reconstruction task, post hoc Bonferroni test p = .018 (for more details, see Indrarathne & Kormos, )—suggests that the S‐shaped curve in the last session represents not only an attenuation of attention but an observable increase in processing efficiency. The number of exposures after which this high level of processing efficiency seems to be achieved bears very close resemblance to the findings of Godfroid et al.’s () study, where they also detected a sudden drop in TFD between Exemplars 16 and 23.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The pattern of correlations between the learning gains and the TFD and ΔTFD values (see Table ) as well as the fact that there were significant learning effects in both tasks—grammaticality judgment task, t (19) = 4.34, p < .001, and sentence reconstruction task, post hoc Bonferroni test p = .018 (for more details, see Indrarathne & Kormos, )—suggests that the S‐shaped curve in the last session represents not only an attenuation of attention but an observable increase in processing efficiency. The number of exposures after which this high level of processing efficiency seems to be achieved bears very close resemblance to the findings of Godfroid et al.’s () study, where they also detected a sudden drop in TFD between Exemplars 16 and 23.…”
Section: Discussionsupporting
confidence: 85%
“…The contextual word‐learning studies in more naturalistic contexts by Godfroid et al. () and Elgort et al. () detected a flattening curve at much later points and indicated the need for a higher number of exposures than does Pellicer‐Sánchez's and our research.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Godfroid et al.’s () and Saragi et al.’s () studies demonstrated clear incidental learning in the highly naturalistic context of reading real novels. However, they lacked experimental control over the number of exposures to the target words, which varied greatly in these authentic novels.…”
Section: Incidental L1 Vocabulary Acquisition From Readingmentioning
confidence: 94%
“…Extensive research using artificial and natural languages has investigated the incidental and intentional learning of vocabulary (e.g., Sonbul and Schmitt, 2013; Hamrick and Rebuschat, 2014; Khezrlou et al, 2017) and grammar (e.g., Indrarathne and Kormos, 2017; Rogers, 2017; Godfroid et al, 2018). Incidental learning refers to the acquisition of knowledge in the absence of the intention to learn, a learning process that tends to result in the development of implicit (unconscious) knowledge.…”
Section: Introductionmentioning
confidence: 99%